O-021 Pipeline embolization of posterior circulation aneurysms: a multicenter study of 131 aneurysms. (23rd July 2017) - Griessenauer, Christoph J; Ogilvy, Christopher S; Adeeb, Nimer; Dmytriw, Adam A; Foreman, Paul M; Shallwani, Hussain; Limbucci, Nicola; Mangiafico, Salvatore; Kumar, Ashish; Michelozzi, Caterina; Krings, Timo; Pereira, Vitor Mendes; et al.
Abstract : Introduction: Flow diversion for posterior circulation aneurysms using the Pipeline Embolization Device (PED) constitutes an increasingly common off-label use for otherwise untreatable aneurysms. Safety and efficacy of this treatment modality has not been assessed in a multicenter study. Methods: A retrospective review of prospectively maintained databases at eight academic institutions was performed from the years 2009 to 2016 to identify patients with posterior circulation aneurysms treated with PED placement. Result s : One-hundred and twenty-nine consecutive patients underwent 129 procedures to treat 131 aneurysms. Twenty-nine dissecting, 53 fusiform, and 49 saccular were included. At a median follow-up of 11 months, complete and near complete occlusion was recorded in 78.1%. Dissecting aneurysms had the highest occlusion rate and fusiform the lowest. Major complications were most frequent in fusiform aneurysms. Minor complications occurred most commonly in saccular aneurysms. In patients with saccular aneurysms, clopidogrel responders had a lower complication rate than clopidogrel non-responders. The majority of dissecting aneurysms were treated in the acute phase following subarachnoid hemorrhage and were associated with the highest mortality rate; however, the rate of other major or minor complications was the lowest among the three aneurysm morphologies. The difference between complications in the ruptured and unruptured group was not statistically significant. Conclusion: In the largest series to date, fusiform aneurysms were found to have the lowest occlusion rate and highest frequency of major complications. Dissecting aneurysms, frequently treated in the setting of subarachnoid hemorrhage, occluded most often and had the lowest complication rate. Saccular aneurysms were associated with predominantly minor complications, particularly in clopidogrel non-responders.